Institutional Profile: UNC Institute for Pharmacogenomics and Individualized Therapy: interdisciplinary research for individual care. (January 2010) - Rakhra-Burris, Tejinder K; Auman, J Todd; Deverka, Patricia; Dressler, Lynn G; Evans, James P; Goldberg, Richard M; Havener, Tammy M; Hoskins, Janelle M; Jonas, Daniel E; Long, Kevin M; Motsinger-Reif, Alison A; Irvin, William J; et al.
The Institute for Pharmacogenomics and Individualized Therapy (IPIT) at the University of North Carolina at Chapel Hill (NC, USA) is a collaborative, multidisciplinary unit that brings together faculty from different disciplines and crosses the traditional departmental/school structure to perform pharmacogenomics research. IPIT investigators work together towards the goal of developing therapies to enable the delivery of individualized medical care. The NIH-supported Comprehensive Research on Expressed Alleles in Therapeutic Evaluation (CREATE) group leads the field in the evaluation of pathways regulating drug activity, and also provides a foundation for future IPIT research. IPIT members perform bench research, clinical cohort analysis and prospective clinical intervention studies, research on the integration of pharmacogenomic therapy into practice and research to foster global health pharmacogenomics application through the Pharmacogenetics for Every Nation Initiative. IPIT Investigators are actively incorporating a pharmacogenomics curriculum into existing teaching programs at all levels.